Financial Determinants and Firm Value Dynamics in JII70 Firms: Earnings Quality Mediation and Investment Opportunity Set Moderation - Ahsan Muhammad; Wiku Suryomurti (Journal of Enterprise and Development (JED), 2026)
Purpose: This study examines the effects of dividend policy, profitability, and liquidity on firm value, using Tobin’s Q as the primary proxy and price-to-book value (PBV) as a robustness check. It further investigates the mediating role of earnings quality and the moderating role of the investment opportunity set (IOS) in both the short run and long run.Method: The population comprises 160 firms listed on the JII70 index during 2018–2024. Through purposive sampling, 16 firms met the selection criteria, producing 112 firm-year observations. The data were analyzed using panel data regression, a Moderated Mediation Model (MMM), and a Partial Adjustment Model (PAM) with STATA 16.Result: The findings show that IOS is the most consistent determinant of firm value across both time horizons. Profitability significantly increases firm value in the long run, while liquidity has a negative interaction with earnings quality when growth opportunities are high. Earnings quality does not significantly mediate the relationship, suggesting that JII70 firm value is driven more directly by growth signals and firm performance than by accounting quality.Practical Implications for Economic Growth and Development: This study implies that managers of Sharia-compliant firms should prioritize investment opportunities and long-term profitability to enhance firm value. Strong growth prospects may provide positive market signals and support sustainable value creation.Originality/Value: This study integrates a Moderated Mediation Model within a dynamic Partial Adjustment Model framework to examine how investment opportunities shape financial determinants of firm value in the Sharia-compliant context.